Book Reviews. (1st September 2012) - Somerville, Keith; Mudiwa, Rudo
SAND STORM: LIBYA IN THE TIME OF REVO LUTION, LINDSEY HILSUM (2012) London: Faber and Faber, 304 pp., ISBN 978571288038, h/bk, £17STARRING MANDELA AND COSBY: MEDIA AND THE END(S) OF APARTHEID, RON KRABILL (2010) Chicago: The University of Chicago Press, 200 pp., ISBN: 9780226451886, h/bk, 60.00, ISBN: 9780226451893, p/bk, 21.00